Palliative care for people with dementia living at home: A systematic review of interventions. (July 2019) - Miranda, Rose; Bunn, Frances; Lynch, Jennifer; Van den Block, Lieve; Goodman, Claire
Background: The European Association for Palliative Care White Paper defined optimal palliative care in dementia based on evidence and expert consensus. Yet, we know little on how to achieve this for people with dementia living and dying at home. Aims: To examine evidence on home palliative care interventions in dementia, in terms of their effectiveness on end-of-life care outcomes, factors influencing implementation, the extent to which they address the European Association for Palliative Care palliative care domains and evidence gaps. Design: A systematic review of home palliative care interventions in dementia. Data sources: The review adhered to the PRISMA guidelines and the protocol was registered with PROSPERO (CRD42018093607). We searched four electronic databases up to April 2018 (PubMed, Scopus, Cochrane library and CINAHL) and conducted lateral searches. Results: We retrieved eight relevant studies, none of which was of high quality. The evidence, albeit of generally weak quality, showed the potential benefits of the interventions in improving end-of-life care outcomes, for example, behavioural disturbances. The interventions most commonly focused on optimal symptom management, continuity of care and psychosocial support. Other European Association for Palliative Care domains identified as important in palliative care for people with dementia, for example, prognostication of dying or avoidance of burdensome interventions were under-reported. No direct evidence on facilitators and barriers to implementation was found. Conclusions: The review highlights the paucity of high-quality dementia-specific research in this area and recommends key areas for future work, for example, the need for process evaluation to identify facilitators and barriers to implementing interventions.